Politics and government - Wood, Richard (Wayland Hove, 1995)
Politics and Government" by Richard Wood (ISBN: 9780750212700) is an educational resource that explores the historical development of political systems and governance structures. Published in 1995 by Hodder Wayland as part of the "Legacies" series, the book examines how ancient civilizations have shaped modern political institutions and governmental frameworks. Through engaging text, illustrations, photographs, and maps, it provides insights into key historical events, influential leaders, and the evolution of political ideologies. Designed for educational use, particularly in alignment with the UK National Curriculum History Key Stage 1, the book encourages readers to understand the foundations of contemporary political systems and their relevance in today's world.